Sociolinguistic Study of the Quechua of Huancavelica - Escobar Zapata, Emérita (2011)
This research is sociolinguistics nature, and the main aim, on the new data recorded in a contemporary talk of Southern Quechua, explains, analyze and discuss, in the light of theories variation and language contact, first the presence of the acute accent in the Quechua District Moya; secondly, the process that affects only partially fricativization to segments /k/, /q/ and /č/, which becomes in its forms /x/, /X/ and /š/, respectively, the method realizes the kind of sociolinguistic variables identified in these phenomena and the way it has conducted data collection.